Educating to sexuality care: the nurse educator’s experience in a multicenter study - Gradellini, Cinzia; Mecugni, Daniela; Castagnaro, Elena; Frade, Fátima; da Luz Ferreira Barros, Maria; Palma, Sara; Bocos-Reglero, María Jesús; Gomez-Cantarino, Sagrario (Frontiers in Psychology, 2023)
Background: Sexuality is an issue inherent in the lives of all human beings. Education for Sexuality takes place informally, through relationships with the environment, with the family as a model, and formally, as a pedagogical practice in Teaching. Education for sexuality is recognized as an instrument of social transformation that leads to changes in behaviors and norms related to sexuality. Objectives: Knowing the perception of nursing professors about sexuality education in professional training, recognizing attitudes of these professors in relation to sexual education and identifying barriers in education for sexuality. Methods: Exploratory and descriptive study, using qualitative methodology. Data collection was carried out from semi-structured interviews and thematic analysis. Results: The interviewees consider sexuality education to be very important, being taught in the nursing course, addressing different themes. In general, they reported feeling comfortable teaching these topics. The identified barriers to the level of education students are in, students' knowledge and reactions to the topic, religious and cultural issues, and the time available to talk about the topic and professional aspects. Conclusion: Sexuality is a fundamental theme in nursing education and needs to be further explored to overcome the barriers associated with its approach.